The performance of control charts with economic-statistical design when parameters are estimated - Mahmoud Al-Said; Rania M. Kamal; Mahmoud M. Rashwan (Review of Economics and Political Science (REPS), 2021)
Purpose This paper presents economic and economic-statistical designs of the adaptive exponentially weighted moving average (AEWMA) control chart for monitoring the process mean. It also aims to compare the effect of estimated process parameters on the economic performance of three charts, which are Shewhart, exponentially weighted moving average and AEWMA control charts with economic-statistical design. Design/methodology/approach The optimal parameters of the control charts are obtained by applying the Lorenzen and Vance's (1986) cost function. Comparisons between the economic-statistical and economic designs of the AEWMA control chart in terms of expected cost and statistical measures are performed. Also, comparisons are made between the economic performance of the three competing charts in terms of the average expected cost and standard deviation of expected cost. Findings This paper concludes that taking into account the economic factors and statistical properties in designing the AEWMA control chart leads to a slight increase in cost but in return the improvement in the statistical performance is substantial. In addition, under the estimated parameters case, the comparisons reveal that from the economic point of view the AEWMA chart is the most efficient chart when detecting shifts of different sizes. Originality/value The importance of the study stems from designing the AEWMA chart from both economic and statistical points of view because it has not been tackled before. In addition, this paper contributes to the literature by studying the effect of the estimated parameters on the performance of control charts with economic-statistical design.
Keywords: 330; Economic-statistical design; Estimation effect; EWMA control chart; Statistical process control